PO033 Do mesiotemporal metabolites explain temporal lobe function after stroke?. (1st December 2017) - Hosseini, Akram A; Wilson, Martin; Ispoglou, Sissi; Hayton, Tom; Evans, Rachel; Sawlani, Vijay; Auer, Dorothee P; Rotshtein, Pia
Abstract : Background: Alterations in brain high-energy metabolism, determined by magnetic resonance spectroscopy (MRS), have biomarker potentials for neurodegenerative disorders. This study is aimed to assess mesiotemporal metabolic integrity in post-stroke cognitive impairment. Methods: 9 patients with post-stroke cognitive impairment and 8 age-matched controls had brain MRI, MRS, and neuropsychometric assessments. Grey matter volume and cortical thickness were measured by FreeSurfer. Single voxel 1H-MRS was used to measure metabolism in the hippocampal areas of both hemispheres. Grey matter volume within the MRS voxel was measured (GM-vol-MRS) and used to correct for partial volume effects on NAA, choline and creatine concentrations. The imaging and cognitive data between the patients and the control group were analysed using spearman correlation analyses. Results: Total hippocampal volume significantly correlated with the mesiotemporal GM-vol-MRS (r=0.833, p=0.005). Increased total choline (r=−0.717, p=0.03) and creatine (r=−0.733, p=0.025) in each left mesiotemporal voxels correlated with left hippocampal volume loss. Raised creatine (r=−0.802, p=0.03) and left hippocampal volume loss (r=0.757, p=0.049) correlated with 'number writing'. Interpretation: Mesiotemporal grey matter volume on the MRS and Free-Surfer seemed to reliably correlate in this pilot study. The alterations in the left mesiotemporal lobe metabolism might correlate with the left meiostemporal cortical thickness and cognitive function.